2013
DOI: 10.17221/6670-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Testing different single nucleotide polymorphism selection strategies for prediction of genomic breeding values in dairy cattle based on low density panels

Abstract: ABSTRACT:In human and animal genetics dense single nucleotide polymorphism (SNP) panels are widely used to describe genetic variation. In particular genomic selection in dairy cattle has become a routinely applied tool for prediction of additive genetic values of animals, especially of young selection candidates. The aim of the study was to investigate how well an additive genetic value can be predicted using various sets of approximately 3000 SNPs selected out of the 54 001 SNPs in an Illumina BovineSNP50 Bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The higher mean EBV accuracies obtained with four GG P80K subsets than with the complete SNP set supported the findings from previous research in dairy [5,2729] and in beef cattle [30] that SNP subsets can yield comparable or higher levels of EBV accuracy than complete SNP sets while lowering genotyping costs.…”
Section: Resultssupporting
confidence: 85%
“…The higher mean EBV accuracies obtained with four GG P80K subsets than with the complete SNP set supported the findings from previous research in dairy [5,2729] and in beef cattle [30] that SNP subsets can yield comparable or higher levels of EBV accuracy than complete SNP sets while lowering genotyping costs.…”
Section: Resultssupporting
confidence: 85%
“…Then, the genomic approach (Schopen et al 2009;Pribyl et al 2010Pribyl et al , 2012Pribyl et al , 2013Matejickova et al 2013;Szyda et al 2013) could be completed by the known major genes concerning milk performance and by the biometric approach (Sigl et al 2012;Meszaros et al 2013;Zavadilova and Stipkova 2013;Zavadilova and Zink 2013). When different effects depending on the breed are found, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, when strongly selected variants were used, the genomic predictions became more biased, with slopes even lower than 0.5. Szyda et al [33] showed that genomic predictions for milk yield were biased when 3 k variants were selected for their effect on milk yield [33]. Brondum et al [32] reported no extra bias when 1623 selected SNPs were added to the 54 k SNP panel, but when the 1623 SNPs were fitted with their own variance in a model with the 54 k SNPs, the bias increased for some traits.…”
Section: Discussionmentioning
confidence: 99%